DEVELOPMENT AND APPLICATION OF SYSTEMIC FAMILY THERAPY - AN ASSESSMENT OF THE SITUATION IN THE EXPIRING SECOND DECADE OF THE 21ST CENTURY AND THE CHALLENGE OF A GENDER-SENSITIVE NEW ORIENTATION - Velasquez-Montiel, S. (Психологія та особистість, 2021)
It is always helpful to take a closer look at the development in order to understand the situation. Therefore, we would like to give a short outline of the development of the systemic therapy, which resulted from the general system theory, at this point, whereby no claim to completeness exists. The general systems theory is based on different scientific methods that initially emerged independently. The considerations of the biologist Ludwig von Bertalanffy can be mentioned as general basics, as well as the concept of cybernetics developed by Norbert Wiener and W. Ross Ashby. These approaches were further developed by the action-theoretical system theory according to Parsons and the introduction of the term «organization» by Luhmann. The aim of general systems theory is to enable more accurate predictions of system behaviour.